Health assessment questionnaire-disability index (HAQ-DI) score at the start of biological disease-modifying antirheumatic drug (bDMARD) therapy is associated with radiographic progression of large joint damage in patients with rheumatoid arthritis. Issue 6 (2nd November 2017) - Nakajima, Arata; Aoki, Yasuchika; Terayama, Keiichiro; Sonobe, Masato; Takahashi, Hiroshi; Saito, Masahiko; Nakagawa, Koichi
Abstract: Objectives: Radiographic progression of damage (RPD) to large joints in patients with rheumatoid arthritis (RA) has not been fully studied. We previously demonstrated that Larsen grade of the large joints was associated with RPD of large joints in patients treated with biological disease-modifying anti-rheumatic drugs (bDMARDs); however, no factors associated with background characteristics of patients were identified. Methods: A total of 400 large joints in the upper and lower extremities, including the shoulder, elbow, knee, and ankle, of 88 patients with RA treated with bDMARDs for 1–3 years were investigated. Radiographs of tender and/or swollen large joints were acquired at least twice during the study period (mean, 16.4 months), and the RPD was evaluated. Results: A multivariate analysis revealed that health assessment questionnaire-disability index (HAQ-DI) score at the start of bDMARD treatment was associated with RPD. The cutoff value that discriminated progression from non-progression, determined by a receiver operating characteristic (ROC) curve, was 1.4375 (sensitivity: 0.778, specificity: 0.894). Conclusions: HAQ-DI score at the start of bDMARD treatment was associated with RPD to large joints during a therapeutic period of 1–3 years. Progressive damage is expected to increase when functional disability exceeds an HAQ-DI score of 1.5.